Duodenal Neoplasms of Gastric Phenotype: An Immunohistochemical and Genetic Study With a Practical Approach to the Classification. (March 2017) - Hida, Risa; Yamamoto, Hidetaka; Hirahashi, Minako; Kumagai, Reiko; Nishiyama, Kenichi; Gi, Toshihiro; Esaki, Motohiro; Kitazono, Takanari; Oda, Yoshinao
Abstract : Duodenal neoplasm of gastric phenotype (DNGP) is very rare, and details of its histopathologic, genetic, and biological features are still unclear. Frequent gene mutations in GNAS, KRAS, and APC have been reported in pyloric gland adenomas and fundic gland-type neoplasms (initially reported as low-grade adenocarcinomas) of the stomach. Here we retrospectively analyzed 16 cases of extra-ampullary DNGP (benign to malignant), and we examined the mucin immunoprofile and oncogene mutations ( GNAS, KRAS, APC, BRAF, and CTNNB1 ). The 16 DNGPs were histologically classified into adenomas (5 pyloric gland adenomas and 2 foveolar-type adenomas), neoplasms of uncertain malignant potential (NUMPs, n=6), and invasive adenocarcinomas (n=3). NUMPs consisted of slightly atypical epithelial cells with pale, eosinophilic, or basophilic cytoplasm growing in an anastomosing or branching glandular pattern, often with expansive submucosal extension. In contrast to invasive adenocarcinomas, NUMPs lacked significant nuclear irregularity, desmoplastic stromal reaction, lymphovascular invasion, and metastasis; their features were reminiscent of fundic gland-type neoplasms of the stomach. Immunophenotypically, most of NUMPs were predominantly positive for MUC6 with variable expressions of pepsinogen-I, H + K + ATPase, human gastric mucin, and MUC5AC. Molecular analyses revealed the gene mutations of GNAS in 6 (38%) of 16 DNGPs (4 [57%] adenomas, 1 [16%] NUMP, and 1 [33%] invasive adenocarcinoma) and APC in 4 of 15 (27%) DNGPs: no adenomas, 2 (33%) NUMPs, and 2 (67%) invasive adenocarcinomas. BRAF mutation was present in only 1 (16%) NUMP, and KRAS and CTNNB1 mutations were absent. In conclusion, gastric-phenotype adenomas and NUMPs of the duodenum are similar to their counterparts of the stomach, in terms of histologic, genetic, and clinicopathologic features. We propose the term "NUMP" as an intermediate category between adenoma and definitely invasive adenocarcinoma. Our findings may provide novel insights into the classification of undescribed but distinctive duodenal tumors showing similarity to gastric-phenotype neoplasms of the stomach. Abstract : Supplemental Digital Content is available in the text.